2016
DOI: 10.19173/irrodl.v17i2.2401
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a Massive Open Online Course in Rural Rwanda

Abstract: The growing utilization of massive open online courses (MOOCs) is opening opportunities for students worldwide, but the completion rate for MOOCs is low .Partners In Health (PIH) implemented a "flipped" MOOC in Rwanda that incorporated in-class sessions to facilitate participant completion.In October 2013, PIH invited its employees, as well as those at the Ministry of Health, to participate in an online MOOC. Each site had at least one volunteer facilitator who accompanied participants throughout the course by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 9 publications
0
37
0
2
Order By: Relevance
“…Not all course content translated easily to online environment; time consuming to design interactive experiences to compensate for no live facilitator; topics that were time-sensitive took effort to maintain but more static material was easier. Participants working together from a single agency enriched the learning experience and learner interaction.Steed 2008 [29] USAMixed method case seriesElectronic survey after experience using Likert scale and open-ended questions7 OTsEvaluate second life virtual reality as a learning methodRural and remoteCultural competencyAttitudes about clients from a different culture perception of learning environment4 themes: sense of presence - embodiment as an African American; Sense of co-presence - self in the environment with others; place presence - natural engagement supporting visual and kinaesthetic learning styles; sense of play - learning through fun - authentic and goal oriented.Warugaba et al 2016 [34] RwandaCohort studyElectronic survey after the education programTotal 38 completed: 17 were AHPsEvaluate an adaptation of a massive open online course including FTF supportRural and remoteGlobal healthAttendance at in-person classes; use of online forum, number of quizzes taken, time required, opinions whether course helps work and career advancement & learning10 / 20 completers used online forums, 18 did up to 7 quizzes; 16 course was helpful to work, 18 course contributes to career advancement; 16 spend 2–5 h a week on course. Relationship between attendance at in-person classes and course completion statistically significant ( p  = 0.013).

Key: AHPs = Allied health practitioners; FTF = face to face; VC = videoconference; TC = teleconference; NR = not reported; MD = Medical Doctor

…”
Section: Methodsmentioning
confidence: 99%
“…Not all course content translated easily to online environment; time consuming to design interactive experiences to compensate for no live facilitator; topics that were time-sensitive took effort to maintain but more static material was easier. Participants working together from a single agency enriched the learning experience and learner interaction.Steed 2008 [29] USAMixed method case seriesElectronic survey after experience using Likert scale and open-ended questions7 OTsEvaluate second life virtual reality as a learning methodRural and remoteCultural competencyAttitudes about clients from a different culture perception of learning environment4 themes: sense of presence - embodiment as an African American; Sense of co-presence - self in the environment with others; place presence - natural engagement supporting visual and kinaesthetic learning styles; sense of play - learning through fun - authentic and goal oriented.Warugaba et al 2016 [34] RwandaCohort studyElectronic survey after the education programTotal 38 completed: 17 were AHPsEvaluate an adaptation of a massive open online course including FTF supportRural and remoteGlobal healthAttendance at in-person classes; use of online forum, number of quizzes taken, time required, opinions whether course helps work and career advancement & learning10 / 20 completers used online forums, 18 did up to 7 quizzes; 16 course was helpful to work, 18 course contributes to career advancement; 16 spend 2–5 h a week on course. Relationship between attendance at in-person classes and course completion statistically significant ( p  = 0.013).

Key: AHPs = Allied health practitioners; FTF = face to face; VC = videoconference; TC = teleconference; NR = not reported; MD = Medical Doctor

…”
Section: Methodsmentioning
confidence: 99%
“…We identified public health training programs delivered in over 11 countries: Australia, 10,16,17 Bolivia, 18 Brazil, 19 Canada, [20][21][22] Greece, 23 the Islamic Republic of Iran, 24 Mexico, 25 Rwanda, 26,27 Uganda, 28 the United Kingdom 29 and the United States of America (USA). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] One program offered trainings in over 77 countries, 46 and another trained participants in Austria, Lithuania and the Netherlands.…”
Section: Public Health Training Program Characteristicsmentioning
confidence: 99%
“…The objectives of and the methods used to gather evaluations varied across studies. Approaches to evaluation included surveys; 26,27,38,42,43 pre/post questionnaires; 30,31,33,41 participant completion statistics; 19 interviews; 28,45 and mixed methods (a combination of either focus groups or interviews and surveys or questionnaires with participants). 9,10,[16][17][18][20][21][22][23][24][25]29,32,[34][35][36]39,40,44 Evaluations after participation captured participants' demographic information, subject knowledge before and after training, satisfaction with and post-training use of their newly gained knowledge.…”
Section: Evaluation Of Trainingsmentioning
confidence: 99%
“…Several synonyms have been coined by researchers for distance learning such as online learning, web‐based learning, distributed learning, massive open online courses and electronic learning or e‐learning. Warugaba, Naughton, Gauthier, Muhirwa, and Amoroso () reported the benefits and utilization of a massive open online course (MOOC) in rural Rwanda. Their study showed the need for internet access, in‐class guidance and employers’ engagement for the successful implementation of MOOCs for capacity‐building in a resource‐limited area.…”
Section: Literature Reviewmentioning
confidence: 99%